Identificación y control in vitro del agente causal de seca y marchitez de la lechuga (Lactuca Sativa l.), en Lamas - San Martín - Flores Saavedra, Dick Fermin (2012)
This research work was carried out in the farm "The Pacific", district and province of Lamas, San Martin Region, in soil texture sandy clay loam, with median availability of elements (NPK), with dry and wilt problems of lettuce plants (Lactuca sativa L.). Objectives: 1. Identify and describe the causal agent of wilt and dry lettuce (Lactuca sativa L.) under laboratory conditions at the National University of San Martin - Tarapoto. 2. - Identify and describe the causal agent of wilt and dry lettuce (Lactuca sativa L.) under laboratory conditions at the National University of San Martin - Tarapoto. The experimental design was completely randomized block with 4 treatments and 3 replications T1 (traditional seedbed and planting bare root), T2 (seedbed planting in trays and covered root (humus 2 * 1)), T3 (seedbed planting in buckets and root cover (2% formalin)), T4 (seedbed planting in trays and covered root (soil solarized 2 * 1)). The planting distance was 0.20 m between row and 0.20 m between plants. Using the "Test of Pathogenic Microorganisms isolated", is tube 4 study treatments T1 (control), T2 (Pythium sp.) T3 (Erwinia sp.) and T4 (Fusarium solani), obtaining laboratory at 100% pathogen incidence in T2 (Pythium sp.) with root rot, stem injuries, dwarfism, leathery leaves and bitter, concluding wilt and plant dry. Reporting finally Pythium sp. as the pathogen culture study. The treatments that I control and achieved higher yields, with benefit - cost to determine the proper control of T2 (seedbed planting in trays and covered root (humus 2 * 1)), concluding with gains of over 30%.